Determination of Elastic Modulus Using Plate Load Test in Calabar, South-Eastern Nigeria - Warmate, T; Nwankwoala, H.O (International Journal of Natural Sciences Research, 2014)
This study evaluates the use of plate load test in ascertaining elastic modulus, Es of a site in Calabar, Niger Delta, Nigeria. The area depicts a coastal plain environment with typical sandy and clayey formation. Four plate load test was carried out within the area of investigation , with load settlement curve which indicates a firm to stiff partial cohesive soil. The result shows geotechnical properties of the soil which depicts values above the A line plot on the plasticity chart. The average liquid limit and the plastic limits values of 30.65% and 15.9% respectively shows that the soil under consideration is low in compressibility. The average moisture content of soil is low. An average elastic modulus value of 4302.289 KN/m2 was obtained in the elastic range (initial tangent modulus), which is indicative of a firm clay . This value conform reasonably with those obtained by method proposed using Cone Penetrometer Test (CPT) with an average cone value of 17Kg/cm2 with Es= 4165 KN/m2. Generally, geotechnical parameters of the soil reflects the nature of the load settlement curve obtained from the test points. Immediate settlement analysis with Es carried out showed low magnitude of compressibility in the study area.